A behavioral economics intervention to increase pertussis vaccination among infant caregivers: A randomized feasibility trial. Issue 6 (3rd February 2016) - Buttenheim, Alison M.; Fiks, Alexander G.; Burson II, Randall C.; Wang, Eileen; Coffin, Susan E.; Metlay, Joshua P.; Feemster, Kristen A.
Abstract: Objectives: The incidence of pertussis has tripled in the past five years. Infants can be protected by "cocooning, " or vaccinating household contacts with the Tdap vaccine. However, Tdap coverage for adult caregivers of infants is low. This study evaluated the feasibility and impact of interventions informed by behavioral economics (retail pharmacy vouchers for Tdap vaccines and a celebrity public service announcement) to increase Tdap vaccination among caregivers of young infants. Methods: We conducted a randomized controlled feasibility trial among adults attending newborn well-child visits at an urban Philadelphia pediatric primary care clinic who were not previously vaccinated with Tdap. Participants were randomized to one of four conditions: ($5-off Tdap voucher vs. free voucher)×(watching a 1 min video public service announcement (PSA) about Tdap vaccination vs. no PSA). Tdap vaccination was assessed by tracking voucher redemption and following up with participants by phone. Results: Ninety-five adult caregivers of 74 infants were enrolled in the study (mean age 29.3 years; 61% male; relationship to newborn: 54% father, 33% mother, 13% grandparent or other; caregiver insurance status: 35% Medicaid, 34% private insurance, 32% uninsured). Only 1 subject redeemed the retail pharmacy Tdap voucher. Follow-up interviews suggest that, even with the voucher, significant barriers to vaccination remained including: delaying planned vaccination, perceived inconvenient pharmacy locations, and beliefs about pertussis risk and severity. Conclusions: Despite leveraging existing infrastructure for adult vaccination, results suggest that retail pharmacy vouchers delivered during a newborn visit are not an effective strategy for promoting Tdap. Alternate approaches are needed that prioritize convenience and provide an immediate opportunity to vaccinate when motivation is high.